Physicochemical properties, cooking parameters, sensory characteristics, and acceptability of rice-like grains from corn [Zea mays L.] - Maloles, Bethlehem P.; Hurtada, Wilma A. (2018)
Rice-like grains are a potential substitute to rice as a quality protein source without sacrificing carbohydrate and fat content. In this study, 11 different combinations of rice-like grains were produced from IPB Var 6 (a non-waxy white corn) and Lagkitan (a waxy white corn). Physicochemical properties (gel consistency and gelatinization), cooking parameters (optimum cooking quality, cooking time, vol- ume expansion, water absorption, and solubility index), sensory characteristics, and acceptability of each corn-based rice-like grain combination were determined. Results show that rice-like grains with higher IPB Var 6 proportions exhibited higher amylose content and are relatively more non-sticky or harder when cooked. Based on gel consistency, composites with higher amounts of IPB Var 6 were classified under rice-like grains that yield less tender cooked grains. In addition, composites with higher IPB Var 6 content have lower gelatinization temperature, required more water to be cooked, and expanded more during cooking. Generally, rice-like grains with 30CO:70CW proportion showed the highest preference score in terms of acceptability based on a seven-point Hedonic rating scale.
Keywords: Corn--Varieties